Safety of plasma-derived factor concentrates - Spannagl, M.; Joch, Ch.; Heindl, B. (Hämostaseologie, 2006)
Elaborate measures for donor selection and the production of clotting factor concentrates have led to a high safety standard of these products. A multimodal approach to eliminate unwanted contents has been established by strict screening of possible donors and various inactivation procedures within the production process. The systematic registration of adverse events shows very few allergic and nonallergic reactions to plasma derived clotting factor concentrates. In none of the registered cases transmission of infections could be verified. The worldwide registration of such adverse events is not yet sufficiently established, since adequate structures are lacking in some countries. According to estimates, far less than half of occurring adverse events are registered in Germany. A European solution in the form of an official register is about to be introduced.
Keywords: Plasma products; pharmacovigilance; inactivation process; donor screening